Physical Activity and Junk Food Consumption Patterns with the Incidence of Adolescent Obesity - Patrichia, Yolanda; Yuliantini, Emy; Krisnasary, Arie; Yunianto, Andi Eka (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Obesity results in a risk of cardiovascular disease such as hypertension and metabolic disorders such as kidney disorders, cancer and potentially social phobia disorders.  The incidence of obesity in adolescents is considered serious because it will continue into adulthood. Obesity can occur because teenagers do less physical activity and eating patterns that often consume junk food. This study aimed to determine the relationship between physical activity and junk food consumption patterns and the incidence of adolescent obesity in SMA Negeri 1 Bengkulu City in 2023. This research used a case control research design. Research subjects whose nutritional status was obese were identified in the past to determine the presence of risk factors. The subjects for this research was class X and class XI of SMAN 1 Bengkulu City with 76 subjects using purposive sampling technique.  Data analysis used the Chi-square test. The results of this study indicated that there was a relationship between physical activity and the incidence of adolescent obesity at State Senior High School 1 Bengkulu City in 2023 (p-value=0,005, OR=4,632) and there is a relationship between junk food consumption patterns and the incidence of adolescent obesity at SMAN 1 Bengkulu City in 2023 (p-value=0,000, OR=6.981). Teenagers in Bengkulu City 1 Public High School mostly do not strenuous physical activity, and almost some teenagers often eat junk food. Suggestions for subjects include education to increase knowledge and attention to the importance of regulating physical activity and eating patterns as well as optimizing nutritional status.